Wolność religijna a nauczanie w szkole - Sobczyk, Paweł (Prawo Kanoniczne, 2008)
In its individual and collective dimensions, religious freedom is a constitutional matter. It is one of the fundamental human rights, and defines the principles of the relationship between the state and churches and other religious organisations. Religious freedom remains closely connected with the concept of school education, the teaching of religion in kindergartens and public schools, the religious education of adults, religious practices of children and young people when on holidays, and religious schools. Among the specific issues are, above all, the legal status of religion teachers, the legal status o f religious school teachers and students, and the status of religion as a school subject. In his study, the author discusses the following issues: the concept and basis of religious freedom, the family, parents, and children as subjects o religious freedom, the state as a competence subject with regard to religious freedom, and the present problems and remarks de lege ferenda.